Chayote—A Potential Vegetable Crop for Florida: HS1454, 12/2022 - Qiu, Yuheng; Liu, Guodong (EDIS, 2022)
Chayote, known as the vegetable pear, is a nutritious plant with a pale-green, ridged, fleshy fruit with a single seed. Florida’s suitable climate combined with chayote’s excellent taste and nutrition indicate that it could be an economically viable crop for commercial production. The intended audience of this new 10-page publication of the UF/IFAS Horticultural Sciences Department is vegetable growers, Extension agents, certified crop advisors, crop consultants, environmentalists, agricultural policy makers. Written by Yuheng Qiu and Guodong Liu. https://edis.ifas.ufl.edu/hs1454